Pembuatan Aplikasi Sistem Pakar Untuk Diagnosa Penyakit Gigi dan Perawatan Gigi - Steven Triyadi Edijanto; Leo Willyanto Santoso; Alexander Setiawan (Jurnal Infra, 2015)
Teeth are hard part that are inside the mouth and got a varied structure also has the possibility to do many jobs. Teeth has a really important role for human life and it is certainly very dangerous if our teeth are having problems, given the fact that teeth disease can cause death. But with the minimum knowledge and information it is impossible to keep our teeth healthy, so an expert is needed to solve this problem about teeth disease and how to keep the teeth healthy. From the fact above, this last project could help us to diagnose the teeth disease and anticipate the risk of teeth disease by designing and implementing this application. This application made web-based (PHP) by using Dreamweaver and XAMPP as the MYSQL database server. This expert system will give a couple of questions to the patient. After all of the questions answered then the diagnosis with the solution will be shown to the patient that will help the patient to anticipate the teeth disease.